International differences in oversubscription and underpricing of IPOs - Chowdhry, Bhagwan; Sherman, Ann (Journal of Corporate Finance, 1996)
We argue that when the offer price of an initial public offering (IPO) is set many days before the issue closes for bidding by investors, relevant price information leaks and becomes public knowledge before investors have finished bidding for firm's shares. Consequently, there are instances when all investors realize ex ante that the offer price is ‘too low’ and we observe a large oversubscription for the firm's shares, as well as instances when the investors realize that the offer price is ‘too high’ and the issue fails. If failure is costly, then the offering is underpriced in order to reduce the likelihood that the issue will fail. This is in addition to the underpricing, as suggested in Rock (1986), to compensate the uninformed investors for the adverse selection problem they face in the allocation of shares. Our argument thus explains why underpricing may be larger in situations when there is information leakage. We further argue that if the issuer collects the interest float on checks deposited by investors for shares they bid, this interest revenue reduces the cost associated with underpricing and thus provides an incentive to underprice the issue further. Our analysis explains some stylized facts about differences in oversubscription and underpricing across countries and allows us to explore some empirical and policy implications. For instance, we show that the method used in the United Kingdom and in most Asian countries may lead to more underpricing and more extreme levels of oversubscription than the method used for firm commitment offerings in the United States.